What moms can't do - Wood, Douglas, 1951- (New York : Simon & Schuster Books for Young Readers, 2001)
A child ponders the many problems that mothers must deal with in the course of a normal day.
School Library Journal, March 2001.
Booklist, April 2001.
Horn Book, October 2005.
Kirkus Review, December 2000.
1.6
K-3
Keywords: Mothers -- Fiction; Mothers -- Fiction; Mothers -- Fiction; Mothers and sons -- Fiction; Family life -- Fiction